Perancangan dan Implementasi Konfigurasi Wifi Router dan Jaringan Wireless dengan Rb951ui-2nd - Basorudin, Basorudin; Rouza, Erni; Yanto, Budi; Mustafa, Satria Riki (Building of Informatics, Technology and Science (BITS), 2021)
Computer networks are growing very rapidly, both in commercial institutions, the academic world, and even people's homes that need internet access. The internet is accessed by many people without exception of hackers and crackers.[1] In the configuration, the output generated is in the form of making a homepage for hotspot user logins, firewalls, namely blocking sites, RADIUS, Blocking internet access at a predetermined time and making SSID. This configuration is very necessary when we access the internet, especially for schools, because with the construction of this configuration, we can limit the use of internet access hours, and students are not allowed to access certain sites during study hours, for example YouTube, Facebook and others, with this configuration Wifi routers and teachers' wireless networks can also limit who can access the internet on certain days and certain hours, especially at SMK N 1 Pendalian 4 Koto. From the results of the trials that have been carried out, it shows success, starting from the internet connection test, both ping to the router and pinging to google, and also when teachers and students access the internet via hotspot login with the voucher that has been provided also successful, then the test results for time restrictions internet access has also been successful, site blocking has also been successfully carried out. So it can be concluded that the research on wifi router and internet configuration at SMK Negeri 1 Pendalian IV Koto has been successful